The impact of facial expressions and emotion incongruence in advertising attention and intention - Mendes, G.; Guerreiro, J.; Loureiro, S. M. C. (Proceedings of the 48th EMAC Conference, 2019)
Facial expressions reflect our emotional state and are hardly controlled. When an individual is not being truthful, there might be incongruences between his speech and his facial expressions. In the era of the Internet where influencers convey important brand messages, incongruences may endanger brand positioning. The current study explores how incongruence may impact on consumers purchase decision, focusing in incongruences between spoked language and facial expressions. An experiment was conducted on 81 participants that watched a congruent and an incongruent ad. Participants were monitored with eye-tracking technology and invited to fill a survey to measure levels of trust, perceived quality, attention and word-of-mouth intentions. A PLS-SEM showed that the congruency has a pivotal effect in purchase decision, as well as in the previously mentioned variables. Therefore, we conclude that an incongruence between spoked and non-spoked language have a negative impact in the consumer decision and opinion about the product.